1997
DOI: 10.1002/(sici)1097-0231(19970615)11:9<1007::aid-rcm954>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Structural heterogeneity, post-translational modifications, and biological activities of SV-IV, a major protein secreted from the rat seminal vesicle epithelium

Abstract: The primary structure of purified SV-IV, a major secretory protein synthesized by the rat seminal vesicle (SV) epithelium, was analysed by electrospray mass spectrometry (ES-MS). The protein was found to be highly heterogeneous. The various components were separated and identified by reversed phase high-performance liquid chromatography (HPLC) on line with ES-MS. Structural characterization of the SV-IV cyanogen bromide digests revealed the occurrence of a Val/Met substitution in about 50% of the purified prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…This finding suggests a physiological role of P1-16 in the homeostatic control. It was reported that the semen contains a thrombin-like enzyme, prothrombin fragments 1 and 2 (F1 + 2), D-dimer (DD) and thrombin-AT (TAT) complexes as well as the seminal vesicle proteins (Ferranti, 1997). These proteins may have roles in seminal clotting and in liquefaction through "fibrinolytic" activity, which may ultimately affect fertility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests a physiological role of P1-16 in the homeostatic control. It was reported that the semen contains a thrombin-like enzyme, prothrombin fragments 1 and 2 (F1 + 2), D-dimer (DD) and thrombin-AT (TAT) complexes as well as the seminal vesicle proteins (Ferranti, 1997). These proteins may have roles in seminal clotting and in liquefaction through "fibrinolytic" activity, which may ultimately affect fertility.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown with hydrolytic experiments that the modulating effect on the coagulation of the protein is located in its 1-70 N-terminal fragment (Di Micco, 1994. Mass spectrometry analysis of purified SV-IV demonstrated that it is highly heterogeneous (Ferranti, 1997). Truncated forms of SV-IV are also present and represent about 14% of the total molecules, in detail the 1-16, 1-17, and 1-18 peptides derived from the N-terminus of the protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on the RSV4 (Ferranti et al, 1997;Metafora et al, 2001;Vilasi and Ragone, 2008;Abrescia et al, 1986;Porta et al, 1990;Di Micco et al, 2000;Stiuso et al, 1999;Porta et al, 1994;Metaofra et al, 1987;Suskiewicz et al, 2011) were the result of the collaboration for many years of several groups operating in Naples (Italy). This protein has always shown resistance to reveal details of its three-dimensional structure, despite being attempted many times its crystallization but with no results.…”
mentioning
confidence: 99%
“…We have demonstrated recently by electrospray MS that 10% of the native SV‐IV molecules are phosphorylated in vitro by protein kinase C and that this modification involves only Ser58 [23]. Furthermore, we have unambiguously demonstrated that a Tyr36‐linked phosphate group is present in 14% of all native SV‐IV molecules [24].…”
mentioning
confidence: 99%